2006
DOI: 10.1021/ic0610740
|View full text |Cite
|
Sign up to set email alerts
|

Mononitrosyl Iron Complexes Supported by Sterically Hindered Carboxylate Ligands

Abstract: Complexes that feature a single NO bound to Fe, as postulated in various carboxylate-rich metalloproteins, were prepared by mixing Fe(II) salts, NO, and the sterically encumbered 2,6-dimesitylbenzoate (Mes2ArCO2-). Among the compounds isolated are the potentially useful heterobimetallic synthon Tl(mu-Mes2ArCO2)3Fe(NO) and a novel cubane Fe4(Mes2ArCO2)4(NO)4(mu3-OH)4 that forms in the presence of added H2O and features syn-[FeNO]2 units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…In each cubane structure of 1 – 3 , there exist four μ 3 ‐O bridges and four syn – syn bridging carboxylato ligands (Scheme e). Such a bridging mode of ligands is also observed for cubanes of Co II 4 O 4 ,14d Co III 4 O 4 ,14g Fe II 4 O 4 ,14i and Fe II 3 Fe III O 4 14j but has not been found for Mn II 4 O 4 cubane. Thus, complex 1 is the first example of an Mn II 4 O 4 cubane that has four μ 3 ‐O bridges and four syn – syn bridging carboxylato ligands.…”
Section: Resultssupporting
confidence: 77%
“…In each cubane structure of 1 – 3 , there exist four μ 3 ‐O bridges and four syn – syn bridging carboxylato ligands (Scheme e). Such a bridging mode of ligands is also observed for cubanes of Co II 4 O 4 ,14d Co III 4 O 4 ,14g Fe II 4 O 4 ,14i and Fe II 3 Fe III O 4 14j but has not been found for Mn II 4 O 4 cubane. Thus, complex 1 is the first example of an Mn II 4 O 4 cubane that has four μ 3 ‐O bridges and four syn – syn bridging carboxylato ligands.…”
Section: Resultssupporting
confidence: 77%
“…10,11 Key examples of structurally characterized, S ) 3/2 species with linear FeNO groups include anionic, pseudotetrahedral tristhiolato- 12,13 and triscarboxylato-{FeNO} 7 complexes. 14 To this list must be added the well-known S ) 0 Roussin's black salt anion, [Fe 4 (µ-S) 3 (NO) 7 ] -, [15][16][17][18][19] whose unique linear FeNO unit is believed to be (locally) an S ) 3/2, {FeNO} 7 center. Now, although some of these systems have been studied by quantum chemical methods, 9,11,18 no comprehensive theoretical study has been reported so far, which provided the key motivation for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Against this broad context, a handful of nonheme {FeNO} 7 complexes, both S = 1/2 and 3/2, stand out, which are characterized by essentially linear {FeNO} 7 groups. Thus, the two S = 1/2 complexes [Fe(CN) 4 (NO)] 2− and Fe(dtc-Me 2 ) 2 (NO) (dtc-Me 2 = N , N ′ -dimethyldithiocarbamate) feature strictly linear FeNO units. , Key examples of structurally characterized, S = 3/2 species with linear FeNO groups include anionic, pseudotetrahedral tristhiolato- , and triscarboxylato-{FeNO} 7 complexes . To this list must be added the well-known S = 0 Roussin’s black salt anion, [Fe 4 (μ-S) 3 (NO) 7 ] − , whose unique linear FeNO unit is believed to be (locally) an S = 3/2, {FeNO} 7 center.…”
Section: Introductionmentioning
confidence: 99%
“…Initial synthetic efforts focused on the treatment of CH 2 Cl 2 solutions of [(Me 4 eda)MCl 2 ] n (Me 4 eda = N , N , N ‘, N ‘-tetramethylethylenediamine; M = Fe, n = 2; M = Zn, n = 1) with either 1 or 2 equiv (per metal) of MesCO 2 X (X = Li or Tl; Scheme ). Chloride metathesis was facile for M = Fe and X = Li, but thallium carboxylate was required for M = Zn.…”
mentioning
confidence: 99%